Pigmented Renal Paraganglioma: A Case Report and Review of the Literature - Turhan, Ezgi Işıl; Saraydaroğlu, Özlem; Yavaşcaoğlu, İsmet (Asian Pacific Journal of Cancer Care, 2020)
Aim: Paragangliomas are rare non-epithelial tumors originating from paraganglia cells in various anatomical regions. Pigmented paragangliomas are more rare. We present the second reported case of kidney-induced pigmented paraganglioma in conjunction with literature. Case Report: A 44-year-old female patient with no known systemic disease was evaluated due to palpitations and a mass detected in the right kidney. Surgically, a 6 cm mass localized between kidney middle pol and vena cava inferior was separated from the surrounding tissues. In the sections prepared from the lesion, there were organoid patterned cell islands separated by fibrovascular septa. Brown pigment was evident in most of the tumor cells. Immunohistochemically, tumor cells expressed synaptophysin, chromogranine, NSE. In tumor cells, Mart1 and HMB45 were negative. In the light of all these findings, the case was diagnosed as ‘pigmented paraganglioma’. Discussion: The most common localizations of paragangliomas are carotid body, vagal body, middle ear, Zuckerkandl organ, mediastinum and retroperitoneum. There are 12 cases of intrarenal paraganglioma reported in the literature. Pigmented paraganglioma originating from the kidney has been reported only once. Conclusions: By presenting the second kidney-derived pigmented paraganglioma reported in the literature, we emphasize that the morphological and geographic spectra of these tumors may be large.